Designing cost-efficient mechanisms minimum constraint design, designing with commercial components, and topics in design engineering - Kamm, Lawrence J. (Society of Automotive Engineers, 1993)
A successful engineer and entrepreneur shares his secrets for producing consistently superior designs at substantial cost savings. Minimum constraint design (MinCD) is a new systematic design strategy that yields major cost reductions and greatly improves the reliability of manufactured mechanisms. For the first time, this practical reference provides the "how-to-do-it" information you need to put this powerful design tool to work right away -- no matter what your level of training or experience. Based upon the author's extensive experience in product design, this timely book clearly explains the advantages of MinCD and tells you how to create better, more cost-efficient product designs using readily available commercial components. Packed with original ideas, design tips, helpful examples, and references - including directories of component vendors - this unique blend of practical and theoretical knowledge will revolutionize the way you work.
Title from PDF title page (SAE Web site, 08/03/2012).
Originally published: New York : McGraw-Hill, ©1990.
Keywords: Machine design.; Value analysis (Cost control); elektronické knihy; electronic books